The Influences of Self-Efficacy on Intrinsic Motivation Among Woodball Players in Malaysia (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2023)
This study aims to identify the level of Self-Efficacy and Intrinsic Motivation among woodball players in Malaysia. This study also determined the difference between Self-Efficacy and Intrinsic Motivation, investigated relationship between Self-Efficacy and Intrinsic Motivation and looked at the influence of Self-Efficacy on Motivation among woodball players in Malaysia according to gender. The study sample consisted of 177 woodball players in Malaysia (male=106, female=71) who participated in the Penang Open Woodball Championship 2023 (National Woodball Circuit 1) were randomly selected. Instrument used to measure Self-Efficacy is Athlete Self-Efficacy Scale (ASES) while Intrinsic Motivation uses the Sport Motivation Scale (SMS-28) through the distribution of questionnaires. Research analysis involves descriptive and inferential statistics using t-test, and linear regression using SPSS software. Results of the study show that there is no significant difference between male and female players regarding Self-Efficacy and Intrinsic Motivation. Self-Efficacy does not have a positive relationship with Intrinsic Motivation among male woodball players in Malaysia. For female players, the study shows that there are two dimensions namely Professional Thinking Efficacy (r=-2.152, p<0.05) and Personality Efficacy dimension (r=3.235, p<0.05) have a significant relationship while the other two dimensions do not have a positive relationship with Motivation Intrinsic. Overall, this study shows that all the dimensions found in Intrinsic Motivation namely To Know, To Accomplish and To Stimulating Experience are factors that affect Self-Efficacy among Malaysian woodball players. The results of this study provide information to the woodball sports development department to increase the Self-Efficacy and Intrinsic Motivation of woodball players.